Contamination levels of organophosphorus and synthetic pyrethroid pesticides in cocoa beans from Ghana. (March 2017) - Okoffo, Elvis D.; Fosu-Mensah, Benedicta Y.; Gordon, Christopher
Abstract: The concentrations of pesticide residues in fermented dried cocoa beans were assessed from sixteen (16) selected cocoa farms in the Dormaa West District in the Brong Ahafo Region of Ghana. The samples were extracted and analysed for 13 organophosphorus and 9 synthetic pyrethroid pesticide residues using a partially modified multi-residue method for agricultural chemicals by a Varian CP-3800 Gas Chromatograph equipped with a pulse flame photometric detector (PFPD) and 63 Ni electron capture detector (ECD), respectively. The study revealed the presence of three organophosphorus pesticide residues namely; chlorpyrifos (0.04 mg/kg), pirimiphos-methyl (0.03 mg/kg) and diazinon (0.01 mg/kg), with chlorpyrifos occurring most frequently, and six synthetic pyrethroid pesticide residues namely; allethrin (0.01 mg/kg), lambda-cyhalothrin (0.03 mg/kg), deltamethrin (0.03 mg/kg), cypermethrin (0.04 mg/kg), bifenthrin (0.02 mg/kg) and permethrin (0.02 mg/kg), with cypermethrin occurring most frequently. None of the detected pesticides' average residues did exceed their European Union Maximum Residue Limits for cocoa beans. Considering levels of pesticide residues in the fermented dried cocoa beans analysed against the European (EU) commissions' regulations on pesticides residues, cocoa beans from the study area will not pose any significant threat to the cocoa industry in Ghana as far as shipment to Europe is concern. The presence of organophosphorus and synthetic pyrethroid pesticide residues in the cocoa bean samples analysed could be attributed to their usage by cocoa farmers in the study area. The routine monitoring of pesticide residues in the study area is necessary for the prevention, control and reduction of environmental pollution, so as to minimize health risks. Highlights: Organophosphorus residues detected were chlorpyrifos, pirimiphos-methyl, diazinon. Chlorpyrifos was the most frequently occurring organophosphorus residues. Six synthetic pyrethroids pesticide residues were detected in the cocoa bean. Cypermethrin was the most frequently occurring synthetic pyrethroids residues. None of the pesticides residues exceeded EU MRL for cocoa beans.